Tourist routes in Puntarenas: an opportunity for the inclusion of women - Elizondo Ezpinoza, Valerie (2022)
This article contemplates a strengthening of Natalia Mairena's thesis proposal, Jale al Puerto, by including natural, cultural and social inputs that were not considered in the first instance. Thus, such strengthening bets on the inclusion of women in the project, since at the country level the Cultural Information System of Costa Rica (2014) identifies various organizations of cultural management and production, many of these of women entrepreneurs; several of these are representatives of the province of Puntarenas, such as the Association of Vigoroneras and Cajeteras de Puntarenas or the Liga de Mujeres of the canton of Puntarenas. Therefore, it is recommended that an organized group of women from Puntarenas collaborate in the development of the proposals in conjunction with other public agencies, in order to benefit the integration of women in the economy of Puntarenas and manage a space for the empowerment of women in Puntarenas.